Temperature field analysis of an air-water composite cooling high-speed generator - Tang Chenqi; Yu Zhongjun; Fu Jia; Yang Juntan; Jiang Hao (Case Studies in Thermal Engineering)
With the increase in the power density of the generator, the operation safety and the service life of the generator are increasingly affected by its internal temperature rise. For high-speed hybrid excitation synchronous generators, the stator includes armature windings and annular excitation windings, which makes heat dissipation difficult and requires the design of an efficient heat dissipation structure. An air-water composite cooling structure is proposed for this purpose. The air-cooled section is a cooling structure with inlets at both sides and radial ventilation. The water-cooled section includes cooling water pipes.To better analyze the generator's flow field, a model of the water pipe is established to study the flow characteristics of the cooling water inside the pipes. In addition, a model of the air is established, and its flow characteristics inside the generator are analyzed. To better evaluate the cooling effect, simplified models are established to compare and analyze the temperature field of generators with the air-cooled, water-cooled, and air-water composite cooling structures. The influence of the ventilation area on the stator back on the flow and temperature fields is studied. The results indicate that it’s appropriate to select 2.09 m/s as the inlet flow rate, and the pressure difference is 74508.19Pa. The airflow at the back of the stator is the highest, nearly 2.4 times higher than that at the air gap. The heat dissipation requirement cannot be achieved alone by the air-cooled or water-cooled structure, but it can be done by the air-water composite cooling structure. Under the condition that the heat dissipation requirement is met, the required air-cooled pressure can be reduced by appropriately increasing the ventilation area on the stator back. Finally, the reliability of the simulation results is verified through experimental results.